Improving User Comfort Classroom at the Kalimantan Institute of Technology with Maintenance Factors - Oryza L Sari; Bobby Zafnat Fanneah Elwore; Basyaruddin Basyaruddin (U Karst, 2021)
In building construction, the implementation of maintenance activities plays an important role in the quality of the building. By carrying out these activities regularly, it’s hoped to minimize and prevent damage to buildings and make users feel comfortable. Kalimantan Institute of Technology must have comfortable study spaces. This study aims to determine the effect of the class maintenance factor on the user's comfort level. The analysis brought by determining what factors are influencing, these factors influence, and the most dominant factors affecting the most. Primary data was obtained by distributing questionnaires to respondents, secondary data inactive students, and lecturers at the Kalimantan Institute of Technology, and supporting research data in ministerial regulations, books, research journals, and others. The data analysis process uses IBM SPSS as an auxiliary program with multiple linear regression analysis methods. Based on the research and data processing conducted, it’s concluded that 8 factors influence the maintenance, namely the maintenance of user comfort by 80.8% and the variable maintenance of the room walls. The room wall maintenance variable is the most dominant factor influencing the comfort of classroom users. Knowing these factors can implement optimal implementation to support the comfort of class users at the Kalimantan Institute of Technologists.